A Study and Comparative Analysis of the Action of the Deacidifying Products Bookkeeper® and Nanorestore Paper® on Plant Textile Fibres - A. Nani; C. Ricci; A. Gatti; A. Agostino (Heritage, 2025)
The aim of this study is to evaluate the effectiveness of deacidifying treatments for the restoration of textiles used as supports for works of art, with particular attention to the chemical stability, colour variation and mechanical resistance of the materials over time. The present study involved the analysis of two products: BookkeeperTM, containing magnesium oxide, and NanorestoreTM, a dispersion of calcium hydroxide in alcoholic solutions of ethanol and 2-propanol. The products were applied to a series of tests on cotton, linen and jute fabrics. The experimental approach comprised an artificial degradation process of the fabrics, followed by the application of the treatments and an accelerated ageing cycle. A series of parameters were monitored throughout the experiment, encompassing surface pH, chromatic shifts ascertained through colorimetric measurements and the morphological transformations of the fabrics, as elucidated by scanning electron microscopy (SEM-EDS). The findings yielded from this study have enabled the delineation of the behaviour exhibited by the treated materials over an extended timeframe. This underscores the significance of a judicious selection of treatments, contingent upon the particular chemical and physical attributes inherent to the fabrics in question.